Role of fibreoptic bronchoscopy in haemoptysis: an analysis of 157 patients - Shah, Naveed Nazir; Wani, Manzoor Ahmad; Khursheed, Syed Quibtiya; Bargava, Rakesh; Ahmad, Zuber; Dar, Khurshid Ahmad; Bachh, Arshad Altaf (International Journal of Research in Medical Sciences, 2017)
Background: Objectives of this study were to define the role of fibreoptic bronchoscopy (FOB) in determining the etiology of haemoptysis, to determine whether bronchoscopy is useful in haemoptysis with normal chest x-ray, to determine whether early bronchoscopy is better than delayed bronchoscopy. Methods: This prospective study was conducted on 157 patients who presented with hemoptysis to the Department of Tuberculosis and Chest diseases. All these patients underwent FOB after taking proper history and examination and ruling out any contraindication to the procedure. Results: In patients with haemoptysis with normal CXR, a diagnosis was established in 54.5% by FOB while 38.6% had a normal bronchoscopy. An endoscopic diagnosis of bronchitis was made in 22.7% patients. In only 9.1% patients an endobronchial mass was seen on bronchoscopy, and all of them were more than 40 years of age. Active bleeding/bleeding site was localized in 18.1% patients. In patients with abnormal chest roentgenogram who underwent FOB, a definitive diagnosis was established in 75.4% cases with active bleeding/ bleeding site localized in 59.6%. Thirty five percent were having an endobronchial mass. Of all the patients who underwent FOB for recurrent haemoptysis, active bleeding/bleeding site was localized in 48.4% patients. Bleeding site was localized in 62.9% patients who underwent early FOB, while the yield was lower (29.4%) in patients who underwent delayed FOB. Conclusions: Fibreoptic bronchoscopy (FOB) is an important and useful investigation in patients of haemoptysis in determining the bleeding site and etiology of haemoptysis. Early FOB has higher yield in localizing the bleeding site than delayed FOB.